Pharmacogenomics of cisplatin‐induced neurotoxicities: Hearing loss, tinnitus, and peripheral sensory neuropathy - Xindi Zhang; Matthew R. Trendowski; Emma Wilkinson; Mohammad Shahbazi; Paul C. Dinh; Megan M. Shuey; Regeneron Genetics Center; Darren R. Feldman; Robert J. Hamilton; David J. Vaughn; Chunkit Fung; Christian Kollmannsberger; et al. (Cancer Medicine, 2022)
Abstract Purpose Cisplatin is a critical component of first‐line chemotherapy for several cancers, but causes peripheral sensory neuropathy, hearing loss, and tinnitus. We aimed to identify comorbidities for cisplatin‐induced neurotoxicities among large numbers of similarly treated patients without the confounding effect of cranial radiotherapy. Methods Utilizing linear and logistic regression analyses on 1680 well‐characterized cisplatin‐treated testicular cancer survivors, we analyzed associations of hearing loss, tinnitus, and peripheral neuropathy with nongenetic comorbidities. Genome‐wide association studies and gene‐based analyses were performed on each phenotype. Results Hearing loss, tinnitus, and peripheral neuropathy, accounting for age and cisplatin dose, were interdependent. Survivors with these neurotoxicities experienced more hypertension and poorer self‐reported health. In addition, hearing loss was positively associated with BMIs at clinical evaluation and nonwork‐related noise exposure (>5 h/week). Tinnitus was positively associated with tobacco use, hypercholesterolemia, and noise exposure. We observed positive associations between peripheral neuropathy and persistent vertigo, tobacco use, and excess alcohol consumption. Hearing loss and TXNRD1, which plays a key role in redox regulation, showed borderline significance (p = 4.2 × 10−6) in gene‐based analysis. rs62283056 in WFS1 previously found to be significantly associated with hearing loss (n = 511), was marginally significant in an independent replication cohort (p = 0.06; n = 606). Gene‐based analyses identified significant associations between tinnitus and WNT8A (p = 2.5 × 10−6), encoding a signaling protein important in germ cell tumors. Conclusions Genetics variants in TXNRD1 and WNT8A are notable risk factors for hearing loss and tinnitus, respectively. Future studies should investigate these genes and if replicated, identify their potential impact on preventive strategies.